Pelatihan Pendekatan Deep Learning untuk Meningkatkan Kemampuan Berpikir Kritis Anak Usia Dini Pelatihan Pendekatan Deep Learning untuk Meningkatkan Kemampuan Berpikir Kritis Anak Usia Dini - Afifah Rahmaningrum; Nur Ika Sari Rakhmawati; Dewi Komalasari; Muhammad Reza; Dwi Jayanti Kurnia Dewi (Educational Consultant & Counseling Career (EC3) Mataram, 2025)
Early childhood education requires teachers to design learning that stimulates critical thinking skills. However, most PAUD teachers in HIMPAUDI, Depok District, Sleman, have limited understanding of the deep learning approach. This community service program aimed to enhance teachers’ competence in implementing deep learning through theory-based and practical training. The methods included socialization, interactive workshops, and classroom mentoring. The results showed a significant improvement in teachers’ understanding of deep learning concepts and their ability to design learning activities that foster children’s critical thinking. Moreover, teachers successfully developed innovative teaching tools and materials based on the deep learning approach. This program highlights the importance of continuous professional development for early childhood teachers and supports the implementation of 21st-century learning focused on cultivating critical thinking skills from an early age.